Innovations in the Integrated Management of Breast Cancer - Franceschini, Gianluca; Sanchez, Alejandro Martin; Masetti, Riccardo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Breast cancer is acknowledged as an international priority in healthcare. It is currently the most common cancer in women worldwide, with demographic trends indicating a continuous increase in incidence. Over the years, increasing efforts and resources have been devoted to the search for a systematic and optimized strategy in breast cancer diagnosis and treatment. Today, the Breast Unit model is considered the gold standard in order to ensure optimal patient-centered and research-based clinical services through multidisciplinary and integrated management.Surgical treatment has gradually evolved toward less aggressive approaches with the adoption of new therapeutic strategies. The evolution of evidence-based guidelines in such leading disciplines as radiation and medical oncology has led to a steady improvement in survival rates. This Special Issue will highlight innovations in the integrated management of breast cancer, their potential advantages, and the many open issues that still need to be properly defined and addressed.